Mitral Valve Prolapse and Sudden Cardiac Death: A Systematic Review. Issue 23 (4th December 2018) - Han, Hui‐Chen; Ha, Francis J.; Teh, Andrew W.; Calafiore, Paul; Jones, Elizabeth F.; Johns, Jennifer; Koshy, Anoop N.; O'Donnell, David; Hare, David L.; Farouque, Omar; Lim, Han S.
Abstract : Background: The relationship between mitral valve prolapse (MVP) and sudden cardiac death (SCD) remains controversial. In this systematic review, we evaluate the relationship between isolated MVP and SCD to better define a potential high‐risk subtype. In addition, we determine whether premortem parameters could predict SCD in patients with MVP and the incidence of SCD in MVP. Methods and Results: Electronic searches were conducted in PubMed and Embase for all English literature articles published between 1960 and 2018 regarding MVP and SCD or cardiac arrest. We also identified articles investigating predictors of ventricular arrhythmias or SCD and cohort studies reporting SCD outcomes in MVP. From 2180 citations, there were 79 articles describing 161 cases of MVP with SCD or cardiac arrest. The median age was 30 years and 69% of cases were female. Cardiac arrest occurred during situations of stress in 47% and was caused by ventricular fibrillation in 81%. Premature ventricular complexes on Holter monitoring (92%) were common. Most cases had bileaflet involvement (70%) with redundancy (99%) and nonsevere mitral regurgitation (83%). From 22 articles describing predictors for ventricular arrhythmias or SCD in MVP, leaflet redundancy was the only independent predictor of SCD. The incidence of SCD with MVP was estimated at 217 events per 100 000 person‐years. Conclusions: Isolated MVP and SCD predominantly affects young females with redundant bileaflet prolapse, with cardiac arrest usually occurring as a result of ventricular arrhythmias. To better understand the complex relationship between MVP and SCD, standardized reporting of clinical, electrophysiological, and cardiac imaging parameters with longitudinal follow‐up is required.